Replacing antibodies with modified DNA aptamers in vaccine potency assays. Issue 41 (4th October 2017) - Trausch, Jeremiah J.; Shank-Retzlaff, Mary; Verch, Thorsten
Highlights: Aptamers where developed that bind the common vaccine carrier protein CRM197 . Aptamer and antibody affinity for CRM197 is similar, although binding kinetics differ. Aptamers function well in potency type assays, in some formats better than antibodies. The aptamer epitope is adjacent to at least one antibody epitope. Abstract: Vaccine in vitro potency assays are vital regulatory tests that are used to confirm the presence and concentration of an antigen of interest in a form that directly or indirectly relates to protective activity in patients. Current assays come in many forms, but they almost exclusively use antibody reagents for selective detection of the target antigen. Antibodies provide specific recognition of vaccine antigens but also exhibit drawbacks such as stability limitations, cost, and lot-to-lot variation, which can make it challenging to maintain the reagent throughout the lifetime of the vaccine. We explored replacing antibodies with aptamers. Aptamers are macromolecules, such as nucleic acids, which can bind to their targets with high specificity and affinity, similar to that of antibodies. Some of the advantages of using aptamers over antibodies is that aptamers can be more stable, smaller, less expensive to produce, synthesized in vitro, and logistically easier to supply throughout the multi-decade lifespan of a commercial vaccine. We created modified DNA aptamers against the common vaccine carrier protein, CRM197 . Several aptamers were discovered and one was chosen for further characterization. The binding kinetics of the aptamer revealed an off-rate 16-fold slower than anti-CRM197 antibodies used for comparison. The aptamers were more sensitive than available antibodies in some assay formats and comparable in others. The aptamer epitope was mapped to the receptor-binding domain of CRM197, a site adjacent to a known antibody binding site. These data address some key aspects for a path forward in replacing antibodies with aptamers for use as critical reagents in vaccine assays. We further highlight the possibility of using nucleic acid reagents to develop next generation potency assays.